The communicative processes of musicians engaged in synchronous play - Faber, Sarah (2014)
Music is a sophisticated cognitive behaviour that employs extensive bilateral neural networks. Recent research investigating the brain engaged in active music-making, both pre-composed and improvised, has localized this network, and made comparisons to similarities and differences as they relate to the production of language. This study investigated the electroencephalographic data of musicians engaged in dyadic instrumental improvisation. Ten musicians (3 pianists, 5 guitarists, and 2 ukulelists) engaged in dyadic improvisations while data was recorded from one of the pair. Playing conditions were established by the participants, and musical features were extracted from the audio data following the experiment. EEG data showed extensive bilateral activity across the cortex of all participants. Common musical features were analyzed in the EEG data, and evidence of an overall music improvisation process was found with minor differences between instrument groups and conditions.